Tracking Some Phonetic Terms in the Arabic Lesson: A Descriptive Analytical Research (Journal of the College of Education for Women, 2022)
This research aims to shed light on some phonetic linguistic terms used in the Arabic phonetic lesson for the purpose of monitoring, analyzing and tracking its developments. Such a step helps to standardize and weigh between them. The study follows a descriptive-analytical approach; it surveys the problem of the phonetic linguistic term, and its linguistic exactness. Then, it examines some phonetic terms in the Arabic phonetic lesson, such as phonology and phonology; intensity, looseness and mediation; the production, articulatory, transition, position, and the two vocal chords. One of the most prominent conclusions of the study is that the phonetic linguistic terminology enjoyed a tangible development since its infancy, given that phonetics was in the process of emerging and did not reach maturity. Besides, the auditory impression and the western borrowing have a major role in the diversity of the phonetic linguistic terminologies. This is because the multiplicity issue of the linguistic term in general and the phonetic term in particular in Arabic linguistic studies has become one of the problems that Arab researchers suffer from. It has become a source of hesitation whether to choose a given phonetic term or another. This further reflects being unsettled or the lack of agreement on the standards and foundations of the use and translation of the phonetic term. More so, most of the sources on which the research relied on are translated sources that basically reflect the problems of confusion, ambiguity and inaccuracy in the meaning of the term.